The potential of CO2 sequestration from basaltic rock in Peninsular Malaysia - Ahmad Fauzan Yusoff,; Hijaz Kamal Hasnan,; Muhammad Hatta Roselee,; Khairul Azlan Mustapha,; Azman Abdul Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Basaltic rock is a efficient for long-term solution in carbon dioxide (CO₂) sequestration because of its ability to chemically bind CO₂ in stable and form a solid mineral, which minimizes the risk of leakage and for permanent storage. This study investigates the mineralogy and geochemistry of Segamat and Kuantan basalts in Peninsular Malaysia to evaluate their suitability for mineral carbonation. Petrographic and mineralogical analyses indicate basalt contains silicate minerals, which are plagioclase (50-60)%, pyroxene (20-30)% and olivine (10-20)% that are highly conducive to CO2 mineral carbonation. Calcite, magnesite, and siderite are expected to form carbonate minerals through chemical reactions. FESEM analysis shows that basaltic rocks have microcracks and micropores, which are tiny spaces within the rock. These structures provide pathways and space for CO₂ to flow and react with the rock, making it easier for the gas to be stored as solid carbonates. This porosity enhances CO₂ absorption and mineralization, improving the efficiency of carbon sequestration. The strategic location of Kuantan near seawater sources offers unlimited access during CO2 injection activities. Both regions exhibit metaluminous properties that are compatible with a diverse range of mineral carbonation techniques. The Segamat and Kuantan basalts are ideal for CO₂ mineral carbonation due to their reactive silicate minerals, potential for carbonate formation (calcite, magnesite, siderite), and favorable microcrack structures. Their metaluminous, silica-undersaturated composition and Kuantan’s proximity to water sources enhance their potential for effective CO₂ storage and mineralization.